Synergy of Islamic Religious Education Teachers in Fostering Digital Literacy and Research Culture among Students - Bulan, Sri; Zainiyati, Husniyatus Salamah; Kholis, Nur; Anam, Khoirul; Karim, Abdul Rahim; Hasanuddin, Muhammad Irfan (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2024)
Islamic Religious Education (IRE) teachers’ synergy in religious research must be integrated with science, technology, and social sciences and involve collaboration with other subject teachers to produce higherquality research products. This study aims to reveal the role of Islamic Education teacher synergy through digital technology research in developing a culture of literacy and science integration in madrasah aliyah. Qualitative research with a post-positivistic approach was conducted in January 2023 at Madrasah Aliyah Negeri (MAN) Insan Cendekia Pekalongan, Central Java. Primary data were obtained through indepth interviews with the deputy head of student affairs and IRE teachers as research program supervisors. In contrast, secondary data came from documentation of the research results of the Madrasah Young Research (MYRES) team that won a silver medal at the national competition. The results showed that the synergy of IRE teachers in guiding student research could strengthen the culture of religious literacy, such as the study of Surah Maryam verse 23 with the tahlili interpretation approach, semantics, and physiology, which became the basis for the research product “al-Istisyfa” as a relaxation tool for pregnant women. This product integrates religion, science, technology, and social sciences, thus demonstrating the successful integration of various fields of science in religion and technology-based research.